VALIDATION OF PHLEBOTOMINE CARDINAL TEMPERATURES AND HUMIDITIES IN THE REGION OF RIO ARINOS, MATO GROSSO, BRAZIL - Holanda Campelo Junior, Jose; Franck Thies, Sirlei; Djunko Miyazaki, Rosina; Lucia Maria Ribeiro, Ana (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
The purpose of this study was to validate the phlebotomine cardinal temperatures and humidities, reported by Campelo Júnior et al. (2014), using different collection data, obtained in a study on the number of these insects, captured in the Arinos region, in Nova Mutum, Mato Grosso, Brazil, according to spatial (100 m to 1000 m) and temporal (June 2011 to April 2012) variability. Phlebotomines were captured in the riparian forest, by means of 10 traps positioned approximately every 100 m, northwards from the road along the river bank, with samples obtained bimonthly during three consecutive nights for a period of 12 months. Average relative humidity and temperature during the periods when the traps remained at the collection points were measured using a digital thermometer-hygrometer. The phlebotomine sand fly fauna was highly diversified, presenting 31 species, of which Lutzomyia antunesi was the most prevalent (45.4%). L. flaviscutellata, L. whitmani and L. umbratilis, known vectors of Leishmania spp., were also found. There was a marked variation in the quantity of phlebotomines captured throughout the consecutive collection days, as each sampling was affected by different factors determining a different maximum value for the number of insects present in each situation, as demonstrated for temperature and air humidity.